Osseous variations associated with physiological thinning of the glenoid articular cartilage: an osteological study with CT, MRI and arthroscopic correlations - Benes, Michal; Fulin, Petr; Kachlik, David; Al-Redouan, Azzat; Tomaides, Jan; Kysilko, Martin; Salavova, Sarka; Kunc, Vojtech (Skeletal radiology, 2023)
OBJECTIVE: To investigate the relationship between osseous variations of the glenoid fossa and thinning of the overlaying articular cartilage. MATERIALS AND METHODS: In total, 360 dry scapulae, comprising adult, children and fetal specimens, were observed for potential presence of osseous variants inside the glenoid fossa. Subsequently, the appearance of the observed variants was evaluated using CT and MRI (each 300 scans), and in-time arthroscopic findings (20 procedures). New terminology of the observed variants was proposed by an expert panel formed by orthopaedic surgeons, anatomists and radiologists. RESULTS: Tubercle of Assaky was observed in 140 (46.7%) adult scapulae, and an innominate osseous depression was identified in 27 (9.0%) adult scapulae. Upon radiological imaging, the tubercle of Assaky was found in 128 (42.7%) CTs and 118 (39.3%) MRIs, while the depression was identified in 12 (4.0%) CTs and 14 (4.7%) MRIs. Articular cartilage above the osseous variations appeared relatively thinner and in several young individuals was found completely absent. Moreover, the tubercle of Assaky featured an increasing prevalence with aging, while the osseous depression develops in the second decade. Macroscopic articular cartilage thinning was identified in 11 (55.0%) arthroscopies. Consequently, four new terms were invented to describe the presented findings. CONCLUSION: Physiological articular cartilage thinning occurs due to the presence of the intraglenoid tubercle or the glenoid fovea. In teenagers, the cartilage above the glenoid fovea may be naturally absent. Screening for these variations increases the diagnostic accuracy of glenoid defects. In addition, implementing the proposed terminological updates would optimize communication accuracy.
Keywords: kloubní chrupavka; počítačová rentgenová tomografie; Magnetic Resonance Imaging; Bare area; Shoulder Joint; magnetická rezonanční tomografie; Scapula; Humans; dítě; Glenoid fovea; Child; dospělí; Intraglenoid tubercle; Cartilage, Articular; Tubercle of Assaky; lidé; Terminologia Anatomica; Glenoid Cavity; Adult; lopatka; Tomography, X-Ray Computed; Adolescent; Bare spot; ramenní kloub; kloubní jamka lopatky; mladiství